Perjuangan Perempuan Dalam Novel Mereka Bilang Aku Kemlinthi Karya Hanifa Vidya - Aufa Azkia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The following article discusses the results of research on the value of women's struggle in the novel They Bilang Aku Kemlinthi by Hanifa Vidya with a mimetic approach. The focus of this discussion is to describe values ​​which include social reality, educational reality, and the reality of struggle. This approach can be linked between literary works and real life through a mimetic approach. In the novel, the local community rejects the